Ropivacaine with Dexmedetomidine or Dexamethasone in a Thoracic Paravertebral Nerve Block Combined with an Erector Spinae Plane Block for Thoracoscopic Lobectomy Analgesia: A Randomized Controlled Trial [Corrigendum] - Yang J; Zhao M; Zhang XR; Wang XR; Wang ZH; Feng XY; Lei YJ; Zhang JW (Dove Medical Press, 2022)
Yang J, Zhao M, Zhang XR, et al. Drug Des Devel Ther. 2022;16:1561–1571. The authors have advised the affiliation list and correspondence details on page 1561 is incorrect. The correct details are as follows. Jing Yang,1 Min Zhao,1 Xiao-Rui Zhang,1 Xiao-Rui Wang,1 Zhi-Hao Wang,1 Xiao-Yue Feng,2 Ya-Juan Lei,3 Jian-Wen Zhang3 1Department of Anesthesiology, Shanxi Medical University, Taiyuan, 030001, People’s Republic of China; 2Department of Pain Management, Third Hospital of Shanxi Medical University, Shanxi Bethune Hospital, Shanxi Academy of Medical Sciences, Tongji Shanxi Hospital, Taiyuan, 030032, People’s Republic of China; 3Department of Anesthesiology, Third Hospital of Shanxi Medical University, Shanxi Bethune Hospital, Shanxi Academy of Medical Sciences, Tongji Shanxi Hospital, Taiyuan, 030032, People’s Republic of China Correspondence: Jian-Wen Zhang, Department of Anesthesiology, Third Hospital of Shanxi Medical University, Shanxi Bethune Hospital, Shanxi Academy of Medical Sciences, Tongji Shanxi Hospital, No. 99 of Longcheng Street, Xiaodian District, Taiyuan, 030032, People’s Republic of China, Tel +86 13994299284, Email zhangjianwen88_dr@163.com